Beneficial Effects of Adiponectin on Periodontal Ligament Cells under Normal and Regenerative Conditions - Marjan Nokhbehsaim; Sema Keser; Andressa Vilas Boas Nogueira; Joni Augusto Cirelli; Søren Jepsen; Andreas Jäger; Sigrun Eick; James Deschner (Journal of Diabetes Research)
Type 2 diabetes and obesity are increasing worldwide and linked to periodontitis, a chronic disease which is characterized by the irreversible destruction of the tooth-supporting tissues, that is, periodontium. The mechanisms underlying the association of diabetes mellitus and obesity with periodontal destruction and compromised periodontal healing are not well understood, but decreased plasma levels of adiponectin, as found in diabetic and obese individuals, might be a critical mechanistic link. The aim of this in vitro study was to examine the effects of adiponectin on periodontal ligament (PDL) cells under normal and regenerative conditions, and to study the regulation of adiponectin and its receptors in these cells. Adiponectin stimulated significantly the expression of growth factors and extracellular matrix, proliferation, and in vitro wound healing, reduced significantly the constitutive tumor necrosis factor-α expression, and caused a significant upregulation of its own expression. The beneficial actions of enamel matrix derivative on a number of PDL cell functions critical for periodontal regeneration were partially enhanced by adiponectin. The periodontopathogen Porphyromonas gingivalis inhibited the adiponectin expression and stimulated the expression of its receptors. In conclusion, reduced levels of adiponectin, as found in type 2 diabetes and obesity, may compromise periodontal health and healing.